DHEA as a Biomarker of Stress: A Systematic Review and Meta-Analysis - Dutheil, Frédéric; de Saint Vincent, Sarah; Pereira, Bruno; Schmidt, Jeannot; Moustafa, Farès; Charkhabi, Morteza; Bouillon-Minois, Jean-Baptiste; Clinchamps, Maëlys (Frontiers in Psychiatry, 2021)
Background: Psychosocial stress is a significant public health problem inducing consequences for quality of life. Results are conflicting about the use of DHEA as a biomarker of acute stress. We conducted a systematic review and meta-analysis to demonstrate that DHEA levels could be a biomarker of stress. Methods: PubMed, Cochrane Library, Embase, and Science Direct databases were searched on March 19th, 2021, using the keywords “acute stress” AND “DHEA” OR “Dehydroepiandrosterone.” Articles needed to describe our primary outcome, i.e., induction of acute stress and at least two measures of DHEA Results: We included 14 studies, with a total of 631 participants in our meta-analysis. DHEA levels increased overtime after the acute stress (SMD 1.56, 95%CI 1.13 to 1.99). Stratification by time showed a main peak at the end of stress (2.43, 1.59 to 3.27), following by a progressive decrease (coefficient -0.11, -0.19 to -0.17, p=0.020). There was no significant change one hour after the end of the acute stress. Metaregressions showed an impact of mental stress (2.04, 1.43 to 2.65), sex (0.02, 0.00 to 0.04), age (-0.12, -0.2 to -0.05) and obese individuals (0.31, -0.00 to 0.63). There was no difference whatever the type of fluid (blood or saliva) and the technic of measure. Conclusions: DHEA is a biomarker of acute stress, with a short-term increase (1 hour). DHEA increase following acute mental stress, whatever the type and duration of mental stress. Women, young people, and obese individuals had a higher response. Blood and saliva measures were comparable.